Development of Image Processing Algoritm for Determining the Maturity of Fresh Mangosteen - Diding Suhandy; Usman Ahmad (Jurnal Keteknikan Pertanian, 2003)
One of important factor in post harvest handling is cropping at correct maturity level. Fruit maturity relates to age pluck vegetable or fruit to be harvested have old enough or not yet. Grading represent dissociation of product becomes some group quality of pursuant to maturity level, size measure, color, form, heavy, texture, aroma and freedom from foreign object or dirt.The objective of this research is to predict the maturity of fresh mangosteen by means of an image processing algorithm. In this study, four stages maturity (120, 126, 132 and 138 days after flowering) were used as objects with 33,37,40,40 samples for each stages of maturity. The image processing program to analyze the relationship between the maturity and the color, size, and shape of fruits.